GE_GERICHTE C/24151/2017 vom 22. Januar 2019 - GE Cour de justice (2019)
MESURE PROVISIONNELLE ; PARTAGE SUCCESSORAL ; SUSPENSION DE LA PROCÉDURE ; DOMMAGE IRRÉPARABLE | CPC.126; CPC.319b.al2; Cst.29.al2; CPC.261; CPC.269; CPC.604; CPC.551